Experimental Study of Pull-Out Failure on Sanko Hammer Drive Anchor Using Cast in Place and Post-Installed Methods on Ready-mix Concrete with Quality of 25 Mpa - Apriyatno, Henry; Supriyono, Supriyono; Taveriyanto, Arie (Jurnal Teknik Sipil dan Perencanaan, 2021)
Abstract: Anchor serves to connect steel and concrete construction that can transfer steel pull-out load to concrete. Sanko hammer drive anchor usually has been available in the model of expansion that can be installed into concrete with cast in place and post installed methods. The experiment was aimed at comparing pull out failures of Sanko hammer drive expansion anchor using cast in place and post installed installation methods based on pull-out failure behavior. Experimental data were obtained from the pull-out strength test of Sanko hammer drive expansion anchor, compressive strength test and ready-mix concrete split tensile test, adhesion strength test and group anchor pull-out test which consists of four units of anchor with diameter of 10 mm planted 90 mm depth on T concrete beams with dimension of 300 mm x 300 mm x 150 mm as many as three beams for each of them using cast in place and post installed installation methods. The results of the experiment showed that concrete compressive tension value (f’c) is 25.69 MPa, anchor tension value (fu) is 383.25 MPa, anchor adhesion tension value (μ) with cast in place method is 2.25 MPa and post installed method is 1.56 MPa. Theoretically, the damage occurred in pull-out condition; while in the experiment, the test showed a difference in pull-out capacity using cast in place installation method of 38.38 kN with deformation of 13.81 mm, which is higher than theoretical value of 26,083 kN and using post installed method of 36.62 kN with deformation of 8.89 mm, which is higher than theoretical value of 18,084 kN and the experiment indicates that the anchor is perfectly pull-out.